FAKTOR-FAKTOR RESIKO KEJADIAN PREMENSTRUAL SYNDROME PADA REMAJA SMA DARUL HIJRAH PUTERI - Herawati; Safitri, Rizka; Rachmawati, Kurnia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Premenstrual syndrome is a syndrome that occurs in females 2-14 days before menstruation.Factors that affect premenstrual syndrome include sport activity, body mass index, consumptionof salty foods and consumption of sweet foods. The objective of this study was to determine therisk factors of premenstrual syndrome on adolescents Darul Hijrah Puteri High School. Theresearch was observational analytic with restrofektif approach (case control study), purposivesampling method was employed in 32 cases and 32 controls at the Darul Hijrah Puteri HighSchool. The results showed an association between sport activity (p=0,002), body mass index(p=0,005), consumption of salty foods (p=0,001), consumption of sweet foods (p=0,045) andpremenstrual syndrome. Sports activity, body mass index, consumption of salty foods and sugaryfood consumption associated with premenstrual syndrome on adolescents in Darul Hijrah PuteriHigh School.This research useful as a reference for future research on premenstrual syndrome.